2020
DOI: 10.1061/(asce)gt.1943-5606.0002271
|View full text |Cite
|
Sign up to set email alerts
|

Large Deformation Finite-Element Simulation of Displacement-Pile Installation Experiments in Sand

Abstract: Displacement piles are driven to support a wide range of structures. Predicting their axial limiting capacities and load-displacement behavior is critical to many such engineering applications. While field load tests may be conducted to check design assumptions, such tests can prove expensive and difficult to generalize. Numerical analyses undertaken to support design face uncertainty over the potentially important effects of pile installation as no well-developed method exists to predict the stresses applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The study deals with significant deformations or even loss of continuity of the mesh of the finite element method. The behaviour of the pile in the soil is a complex issue, which is still examined by many researchers, especially in the case of displacement piles [3,4]. An installation of displacement piles is more invasive to the surrounding soil than the installation of drilled piles and significantly affects changes in soil parameters and consequently the behaviour (displacement) and capacity of the pile under load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study deals with significant deformations or even loss of continuity of the mesh of the finite element method. The behaviour of the pile in the soil is a complex issue, which is still examined by many researchers, especially in the case of displacement piles [3,4]. An installation of displacement piles is more invasive to the surrounding soil than the installation of drilled piles and significantly affects changes in soil parameters and consequently the behaviour (displacement) and capacity of the pile under load.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was proposed by Krasinski [9] for the numerical modelling of the screw pile installation process; however, a comparison of the simulation results with the field measurements showed that the soil parameters still require additional corrections in the zones next to the pile. Another method, the Press Replace Technique, was introduced in [3]. In this method, using a standard FEM code, the process of pressing piles into sands was modelled.…”
Section: Introductionmentioning
confidence: 99%
“…Large-deformation problems in geotechnical engineering, such as pile penetration, are notoriously difficult to simulate using continuum approaches due to both material and geometrical non-linearities (Monforte et al, 2019) and because of mesh distortion related issues (Yang et al, 2020). To overcome these difficulties advanced numerical methods have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these difficulties advanced numerical methods have been developed. Oliynyk et al, (2021) for example used large deformation PFEM (Particle Finite Element Method) analyses to simulate CPTu tests in structured soils, Ko et al, (2016) simulated pile penetration using the Finite Differences Method (FDM) based on Coupled Eulerian-Lagrangian (CEL) method whilst Yang et al, (2020) adopted the Arbitrary Lagrangian-Eulerian (ALE) method to tackle the same problem. Continuum approaches hence have made progress to tackle the numerical complexities stated above.…”
Section: Introductionmentioning
confidence: 99%
“…One outstanding example is in offshore geotechnics where soils that bear offshore structures, such as anchors and rigs, have to work in large deformation to provide required bearing capacity. Other examples include the post-failure analysis of a slope and pile penetration into soils 5 where large deformation of soils is a reality. Modeling of large deformation has proven to be challenging for conventional mesh-based numerical methods, such as the finite element method (FEM).…”
mentioning
confidence: 99%